Is there a need for a uniform approach to judicial oversight over the execution of the immovable property of a judgment debtor? - Van Loggerenberg, Danie (Daniel Elhardus) (University of Pretoria, 2015)
Dissertation (LLM)--University of Pretoria, 2015.